Differentiation of cirrhotic patients with and without hepatic encephalopathy from the analysis of fine motor patterns: A pilot study with the Leap Motion Controller (Research, Society and Development, 2021)
Aim: analyze the motor precision of cirrhotic patients with or without hepatic encephalopathy (HE), in different severities, through the geospatial capture of the hands. Methodology: The target audience was patients at the Gastroenterology Service of a tertiary hospital in Northeastern Brazil. Data were collected from three groups of patients (A, unidentified EH; B, grade I EH and; C, grade II EH). Motricity data collection was performed with the Leap Motion Controller (LMC). The collected data were composed by the position of 16 points of the hands in three dimensions that, in sequence, were converted into distance between two points. Results: 60 patients with a mean age of 54.6 (± 14.7) years were included. The Kruskal-Wallis and Dunn tests indicated differences in the medians of the variables for the three groups (p < 0.05). The graphical representations show a difference in motor precision between the groups in an index of 100% of the variables, with variations with a tendency of C > B > A in 87.5% of the cases. The frequency of movement of the fingers, of both hands, had the potential to differentiate the groups. Direction is more discriminating than position and speed. Conclusion: The results suggest the possibility of differentiating the classes of patients and that the progression of motor deviation is one of the complications of the worsening of the disease.